THE EFFECT OF TAX PLANNING ON TAX AVOIDANCE WITH TAX AGGRESSIVENESS AS A MODERATOR IN THE PERIOD BEFORE AND AFTER THE TAX AMNESTY - Claudianita, Felicia; Trisnawati, Estralita; Budiono, Herlina (International Journal of Application on Economics and Business, 2023)
The research aims to discover the effect between tax planning, such as permanent difference, temporary difference, and foreign tax-rates differentials moderated by tax aggressiveness on tax avoidance before and after the tax amnesty period. This research obtained from 120 initial samples of companies listed in IDX for 2013-2019 period with purposive sampling method. The result shows that only one research model of permanent difference and tax aggressiveness had a significant negative effect on tax avoidance; some models of temporary difference and tax aggressiveness had a significant positive effect on tax avoidance; three research models of foreign tax-rates differentials had none significant effects on tax avoidance; and only on two models of permanent difference that had not been able moderated by tax aggressiveness towards tax avoidance. Hopefully this research could give advantages on implementing tax planning as an important strategy to consistently provides good signals to the company’s external parties.